Quality of life after intervention with a cochlear implant or hearing aid. (17th January 2016) - Contrera, Kevin J.; Betz, Joshua; Li, Lingsheng; Blake, Caitlin R.; Sung, Yoon K.; Choi, Janet S.; Lin, Frank R.
Abstract : Objectives/Hypothesis: To investigate the impact of hearing aid and cochlear implant use on quality of life in adults. Study Design: Prospective observational cohort study. Methods: One hundred thirteen adults aged ≥50 years with postlingual hearing loss receiving routine clinical care at a tertiary academic medical center were evaluated with the Medical Outcome Study Short Form‐36 before and 6 and 12 months after intervention with hearing aids or cochlear implants. Change in score was assessed using linear mixed effect models adjusted for age, gender, education, and history of hypertension, diabetes, and smoking. Results: A significant increase in Mental Component Summary score was observed in both hearing aid and cochlear implant users from baseline to 12 months, with cochlear implant users increasing nearly twice that of hearing aid users (hearing aid: 2.49 [95% confidence interval: 0.11, 4.88], P = .041; cochlear implant: 4.20 [95% confidence interval: 1.85, 6.55], P < .001). The most substantial increases were observed in individuals with the lowest baseline scores. There was no significant difference in physical component summary score from baseline to 12 months. Conclusions: Treatment of hearing loss with hearing aids and cochlear implants results in significant increases in mental health quality of life. The majority of the increase is observed by 6 months post‐treatment, and we observed differential effects of treatment depending on the level of baseline quality of life score with the greatest gains observed in those with the lowest scores. Level of Evidence: 2b. Laryngoscope, 126:2110–2115, 2016